Tribological and mechanical characteristics of AA6082/TiC/WC -based aluminium composites in dry and wet conditions. (2021) - Rajaganapathy, C.; Vasudevan, D.; Dyson Bruno, A.; Rajkumar, T.
Abstract: The tribological and mechanical characteristics of hybrid metal matrix composite on aluminium alloy 6082 reinforced with titanium carbide (TiC) and tungsten carbide (WC) particles was studied for automotive applications. The hybrid composites were fabricated using stir casting techniques by varying TiC and WC particles. Fabricated samples were prepared as per ASTM standard dimensions to conduct mechanical test such as ultimate tensile strength and hardness. The tribological behavior of the hybrid composites was examined using pin on disc tribometer. Distribution of reinforced particles in hybrid composite was examined with scanning electron microscope (SEM) analysis. The tribological characteristics of specific wear rate and coefficient of friction were examined under dry and wet lubricated conditions. Mechanical characteristics and tribological characteristics of the hybrid composites have significantly improved by the presence of reinforced particles (TiC and WC) respectively.